Multiobjective bayesian optimization to enhance computational efficiency in neural network models - Reis, João Gabriel Rodrigues (2024)
Dissertação (mestrado) — Universidade de Brasília, Instituto de Ciências Exatas, Departamento de Estatística, 2024.